Legal Disharmony in Indonesia's Regulatory Framework: A Ratio Legis Analysis of the Classification of Gambling and the Standard Classification of Business Fields in Indonesia 92000 Vis-À-Vis Criminal Prohibition Under the Penal Code - Diana R.W. Napitupulu (International Journal of Law, Crime and Justice, 2025)
This paper analyzes the legal disharmony between the Indonesian Standard Industrial Classification (KBLI) Code 92000, which classifies gambling as a business activity, and Article 303 of the Indonesian Penal Code (KUHP), which criminalizes gambling. Using a normative legal research method supported by theoretical foundations from legal certainty, legal harmonization, and sociological jurisprudence, the paper explores the philosophical, sociological, and juridical ratio legis behind this classification. The research concludes that the classification under KBLI is administrative and does not legitimize gambling activities. The paper suggests harmonization mechanisms to resolve legal contradictions and ensure regulatory coherence.  Address the normative conflict and avoid further interpretive ambiguities, this paper proposes a series of harmonization mechanisms. First, there should be a revision or annotation of KBLI Code 92000 to clarify that its inclusion of gambling is not a recognition of its legality under Indonesian law. Second, greater inter-agency coordination is necessary, especially between the institutions responsible for economic classifications and those enforcing criminal law. Third, legislative synchronization efforts must be enhanced through the establishment of an integrated legal drafting mechanism to ensure that new or revised regulations do not conflict with existing criminal statutes.